Long-term cancer risk after metal-on-metal hip arthroplasty: a Finnish population-based study with a mean follow-up of 12.8 years - Autio, Elias (My University, 2025)
Metal-on-metal (MoM) hip arthroplasties (HA) were widely used worldwide at the beginning of the century. This nationwide retrospective comparative register-based study aimed to assess the long- term cancer risk among all Finnish patients with any kind of MoM hip device and to compare it with the general Finnish population and patients with conventional total hip arthroplasty (THA). A total of 18,922 patients who underwent MoM HA and 29,247 patients who underwent conventional THA were recorded in the Finnish Arthroplasty Register between 2001 and 2013. Cancer data up to 2021 were extracted from the Finnish Cancer Registry. The relative cancer risk compared with the general population was expressed using the standardized incidence ratio (SIR), and the comparison between the MoM and conventional THA cohorts was expressed as the ratio of SIRs. The overall risk of cancer in the MoM cohort was decreased compared with that of the general Finnish population (SIR 0.91; 95% confidence interval [CI] 0.86 to 0.96). When comparing the cohorts, the overall cancer risk was similar (SIR ratio 0.94; 95% CI 0.88 to 1.00). Basal cell carcinoma and melanoma risks in the MoM cohort were increased compared with that of the general Finnish population (SIR 1.08 and SIR 1.17, respectively). However, the basal cell carcinoma and melanoma risks between the cohorts was similar (SIR ratio 1.05 and SIR ratio 1.20, respectively). MoM HA was not associated with increased overall cancer risk. Longer follow-up periods may be needed to clarify the risks of skin and prostate cancers.